2022
DOI: 10.5194/tc-16-2985-2022
|View full text |Cite
|
Sign up to set email alerts
|

Development of crystal orientation fabric in the Dome Fuji ice core in East Antarctica: implications for the deformation regime in ice sheets

Abstract: Abstract. The crystal orientation fabric (COF) of a polar ice sheet has a significant effect on the rheology of the ice sheet. With the aim of better understanding the deformation regime of ice sheets, the work presented here investigates the COF in the upper 80 % of the Dome Fuji Station ice core in East Antarctica. Dielectric anisotropy (Δε) data were acquired as a novel indicator of the vertical clustering of COF resulting from vertical compressional strain within the dome. The Δε values were found to exhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 59 publications
0
15
1
Order By: Relevance
“…Fujita et al, 2000;Saruya et al, 2022b). Here, we estimated this velocity using the relative permittivity value of ice (∼ 3.147 ± 0.010) considering depthdependent variations in crystal orientation fabrics (Azuma et al, 2000;Saruya et al, 2022a) and temperature within the ice sheet (Motoyama, 2007). Timing errors of the initial trigger in the oscilloscope are possible sources of systematic errors.…”
Section: Initial Data Processingmentioning
confidence: 99%
“…Fujita et al, 2000;Saruya et al, 2022b). Here, we estimated this velocity using the relative permittivity value of ice (∼ 3.147 ± 0.010) considering depthdependent variations in crystal orientation fabrics (Azuma et al, 2000;Saruya et al, 2022a) and temperature within the ice sheet (Motoyama, 2007). Timing errors of the initial trigger in the oscilloscope are possible sources of systematic errors.…”
Section: Initial Data Processingmentioning
confidence: 99%
“…Preferred crystal orientation records deformational history (Alley, 1988), and results in increased plastic anisotropy in glacier ice, affecting its flow in glaciers and ice sheets. Furthermore, fabric and texture contrasts across different climate change events are believed to cause significant variations in the rheology of ice in different ice cores (Azuma et al., 2000; Durand et al., 2007; Paterson, 1991; Saruya et al., 2022; Thorsteinnson et al., 1997). For instance, Paterson (1991) found that the strong, near‐vertical single maximum fabric in ice‐age ice, keeps the grain size small and leads to a strain rate 2.5 times faster than that in Holocene ice under the same stress and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…6). According to analyses of the DF ice core (Azuma et al, 1999;Saruya et al, 2022) or 3-D ice sheet modeling (Seddik et al, 2011), deformation of the ice or flow regime towards the ice bottom is complex. Thus we suggest that both horizontal and vertical ice flow should be complex as well, which may be difficult to represent by using the current formulation of vertical velocity profiles.…”
Section: Discussionmentioning
confidence: 99%